The The Role of Nutritional Intake in Stabilizing Patients with Acute Kidney Failure in Emergency Situations: The Role of Nutritional Intake in Stabilizing Patients with Acute Kidney Failure in Emergency Situations - Rahmat , Rosyadi Aziz (JURNAL KESMAS DAN GIZI (JKG), 2024)
Acute kidney failure (AKI) is a medical emergency characterized by a sudden decline in kidney function that occurs within hours to days. This condition causes fluid, electrolyte, and acid-base imbalances that are potentially life-threatening if not treated quickly and appropriately. This study aims to explore the role of nutritional intake in stabilizing patients with Acute Kidney Injury (AKI) in critical emergency conditions. This study highlights the importance of balanced macronutrient (calories and protein) and micronutrient intake, especially in managing fluid balance and maintaining electrolyte homeostasis. This study also investigates the impact of enteral and parenteral nutrition strategies, assessing their relevance in various clinical scenarios, especially for patients who cannot consume food orally. The study method is an observational analytical design with a prospective cohort approach. The results showed that there were significant differences in serum creatinine levels, GFR, and fluid balance before and after the intervention (p <0.05). However, changes in serum sodium levels did not show significant differences. Proper nutrition significantly contributes to the stabilization of AKI patients in emergency conditions.